Peningkatan Literasi Pencegahan dan Penanganan Kekerasan Seksual di Pesantren Mahasiswa An Najah Purwokerto - Eka Safitri; Nurlaela Nurlaela; Munasib Munasib; Alifah Mutia Hanun (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
Cases of sexual violence are cases that are currently intriguing all circles, including the world of Islamic boarding schools. Islamic boarding schools are in second place after universities. This is a warning and vigilance for the Islamic boarding school world, because the patronage relationships that are built in the Islamic boarding school world are often the trigger. The An Najah Purwokerto Student Islamic Boarding School is one of the Islamic boarding schools which is also occupied by students who are studying at tertiary institutions, being an institution that has a high level of risk based on the percentage of cases in Indonesia. The aim of this community service is to provide education as an effort to prevent cases of sexual violence in Islamic boarding schools. In an effort to assist the government in dealing with cases of sexual violence that are rife in Islamic boarding schools, the service team has proposed this study to be carried out. The implementation of the service was carried out at the An Najah Purwokerto Student Islamic Boarding School with participants from the students who occupy the Islamic boarding school, the ustad and ustadzah and the Islamic boarding school management. Through this activity, it can be a step to mitigate the occurrence of sexual violence in Islamic boarding schools and universities where students study.